Polyphenyl ether / polyamide alloy and preparation method and application thereof

By adjusting the component ratio of polyphenylene ether/polyamide alloy and adding specific reinforcement, an alloy with a bicontinuous phase structure was prepared, which solved the problem that existing materials were difficult to achieve hydrolysis resistance, dimensional stability and welding mark strength at the same time, and significantly improved the stress cracking resistance of the material, which was suitable for the water treatment industry.

CN119955287APending Publication Date: 2025-05-09KINGFA SCI & TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411926693.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

Existing polyphenylene ether/polyamide alloys are difficult to achieve the requirements of hydrolysis resistance, good dimensional stability, high weld mark strength and stress crack resistance at the same time, especially in the water treatment industry.

Method used

By adjusting the weight ratio of polyphenylene ether/polyamide and adding glass fibers, toughening agents, compatibilizers and coupling agents, a polyphenylene ether/polyamide alloy with a bicontinuous phase structure or island structure is prepared to enhance the dimensional stability of the material and the welding mark strength.

Benefits of technology

It achieves good dimensional stability, hydrolysis resistance and weld mark strength of the material, can meet the needs of the water treatment industry, and significantly improves the stress cracking resistance of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a polyphenyl ether / polyamide alloy, which comprises the following components by weight: 20-50 parts of polyphenyl ether; 20 to 40 parts of polyamide; 10 to 40 parts of glass fiber; 3-12 parts of a toughening agent; 0.1 to 2 parts of a compatilizer; 0.2 to 1.5 parts of a coupling agent; wherein the weight ratio of the polyphenyl ether to the polyamide is (1.8-1): 1. The polyphenyl ether / polyamide alloy provided by the invention is good in dimensional stability, good in hydrolysis resistance and suitable for the water treatment industry, and the weld mark strength of the polyphenyl ether / polyamide alloy is greater than or equal to 40MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a polyphenylene ether / polyamide alloy and a preparation method and application thereof. Background Art

[0002] As an amorphous engineering plastic, polyphenylene ether (PPE) has the advantages of acid and alkali resistance, high temperature resistance, moisture and heat resistance, and dimensional stability, but it has high viscosity and is not easy to process. By introducing polystyrene (PS) into PPE, the prepared PPE / PS alloy is very suitable for use in the water treatment industry due to the high fluidity of PS and the advantages of moisture and heat resistance and dimensional stability. However, PPE / PS has the problem of internal stress cracking, which leads to the risk of cracking during use. To address this problem, the material needs to have good stress cracking resistance while meeting the requirements of dimensional stability, hydrolysis resistance, and water pressure resistance.

[0003] In order to solve the problem of stress cracking resistance, some manufacturers use PPA, PA, etc. to replace PS, but they find that PA materials will cause the size of the parts to change after absorbing water, which cannot meet customer needs. Some customers also use PP and other materials as a substitute, but find that the initial size of the material cannot directly meet the requirements.

[0004] The water treatment industry needs an alloy that meets the requirements of dimensional stability, hydrolysis resistance, compressive strength, high weld strength and good stress cracking resistance. PPE / PA alloy can meet the requirements of high compressive strength and good stress cracking resistance, but it is difficult to achieve the requirements of hydrolysis resistance, good dimensional stability and high weld strength at the same time. Summary of the invention

[0005] The object of the present invention is to provide a polyphenylene ether / polyamide alloy which is resistant to hydrolysis, has good dimensional stability and high weld mark strength.

[0006] The present invention is achieved through the following technical solutions: A polyphenylene ether / polyamide alloy, comprising the following components in parts by weight: Polyphenylene ether 20-50 parts; Polyamide 20-40 parts; Glass fiber 10-40 parts; 3-12 parts of toughening agent; Compatibilizer 0.1-2 parts; Coupling agent 0.2-1.5 parts; Wherein, the weight ratio of polyphenylene ether to polyamide is (1.8-1):1; The compatibilizer is selected from at least one of maleate compatibilizers, anhydride compatibilizers, and N-phenylmaleimide.

[0007] Preferably, the weight ratio of polyphenylene ether to polyamide is (1.6-1.2):1.

[0008] Preferably, the compatibilizer is selected from maleate compatibilizers.

[0009] The maleate compatibilizer is selected from at least one of butylene maleate and butylene fumarate; and the anhydride compatibilizer is selected from maleic anhydride.

[0010] The coupling agent is selected from at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent; preferably, the coupling agent is selected from a silane coupling agent.

[0011] The silane coupling agent is selected from at least one of an aminosilane coupling agent and a methoxysilane coupling agent.

[0012] The toughening agent is selected from any one or more of maleic anhydride grafted styrene block copolymers and maleic anhydride grafted ethylene-octene copolymers, wherein the weight content of maleic anhydride is 0.5-3wt%, preferably 1.0-2wt%; wherein the styrene block copolymer is selected from at least one of styrene-butadiene-styrene block copolymers, styrene-ethylene / butylene-styrene block copolymers or styrene-ethylene / propylene-styrene block copolymers.

[0013] Preferably, the polyphenylene ether resin has a melt index of 4-90 g / 10 min at 315° C. and 10 kg as tested in accordance with standard ISO 1133-1-2011. The monomer of the polyphenylene ether resin of the present invention is 2,6-dimethylphenol.

[0014] The polyamide resin is selected from at least one of aliphatic polyamide resins and semi-aromatic polyamide resins; the aliphatic polyamide resin is selected from at least one of PA66, PA46, PA610, PA612, PA56, PA510, PA512, PA910, PA912, PA913, PA914, PA915, PA616, PA936, PA1010, PA1012, PA1013, PA1014, PA1210, PA1212, PA1213, PA1214, PA614, PA613, PA615, PA616, PA5, PA6, PA11, and PA12; the semi-aromatic polyamide is selected from at least one of PA MXD6, PA10T, PA10T1010, PA10T66, PA6T, PA6T66, and PA9T.

[0015] Those skilled in the art may choose whether to add 0-2 parts of an auxiliary agent according to actual needs, wherein the auxiliary agent is selected from at least one of an antioxidant and a lubricant.

[0016] The antioxidant may be: 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; 2,5-di-tert-butyl-4-hydroxybenzyl dimethylamine; diethyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; stearyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; 3,5-di-tert-butyl-4-hydroxyphenyl-3,5-distearyl-thiotriazolylamine; 2,6-di-tert-butyl-4-hydroxymethylphenol; 2,4-di-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylglycerol allyl ether)-1,3,5-triazine; N,N'-hexamethylenebis( 3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid); N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine; octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; triethylene glycol-bis[3-(3,5-dimethyl-4-hydroxyphenyl)propionate]; triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]; 2,2'-thiodiethyl-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, etc.

[0017] The lubricant can be: at least one of a fatty acid and a fatty acid derivative; the fatty acid derivative is selected from at least one of a stearate lubricant and a stearate lubricant, and the stearate lubricant is selected from at least one of calcium stearate, magnesium stearate, and zinc stearate.

[0018] The preparation method of the polyphenylene ether / polyamide alloy of the present invention comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder, with the screw speed being 250-500rpm and the extrusion temperature being 230-290°C, to obtain the polyphenylene ether / polyamide alloy.

[0019] The polyphenylene ether / polyamide alloy of the present invention is used for preparing water treatment equipment, such as HVAC valve pipelines, valve cores, electric meter housings, etc.

[0020] The present invention has the following beneficial effects: The present invention adjusts the ratio of PPE / PA materials and adds a specific compatibilizer so that PPE and PA in the material have a bicontinuous phase structure or a transition state to an island structure, so that the material has good dimensional stability, hydrolysis resistance and weld mark strength, and can meet the industry's dimensional stability, hydrolysis resistance, and water pressure resistance strength requirements. In addition, the combination of glass fiber and resin is further strengthened by a coupling agent to further improve the strength of the material. The prepared enhanced PPE / PA alloy composition has good dimensional stability, hydrolysis resistance, and weld mark strength ≥40MPa, and is very suitable for use in the water treatment industry. DETAILED DESCRIPTION

[0021] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0022] PA66: PA66 U3600 NC001, NVIDIA; PA6: PA6 BE3280, Suzhou Hongsheng New Materials; PA1010: PA1010, DuPont; PA10T: Vicnyl 700-02 NC001, Kingfa Technology; PA6T66: NPD-652, NVIDIA; Polyphenylene ether: melt index at 315°C, 10kg is 20-40g / 10min, PPE LXR040, Bluestar; Fiberglass: ECS10-03-568H, Boulder.

[0023] Toughener A-1: ​​Maleic anhydride grafted styrene-butadiene-styrene block copolymer, homemade: SBS and maleic anhydride were melt-mixed in a mass ratio of 99.5:0.5 at a mixing temperature of 200°C.

[0024] Toughener A-2: Maleic anhydride grafted styrene-butadiene-styrene block copolymer, homemade: SBS and maleic anhydride were melt-mixed in a mass ratio of 99:1.0 at a mixing temperature of 200°C.

[0025] Toughener A-3: Maleic anhydride grafted styrene-butadiene-styrene block copolymer, homemade: SBS and maleic anhydride were melt-mixed in a mass ratio of 98:2 at a mixing temperature of 200°C.

[0026] Toughening agent A-4: maleic anhydride grafted styrene-butadiene-styrene block copolymer, homemade: prepared by melt mixing SBS and maleic anhydride in a mass ratio of 97:3.0, and the mixing temperature is 200°C.

[0027] Toughener B: maleic anhydride grafted styrene-ethylene / butylene-styrene block copolymer, maleic anhydride content is about 0.8%, BCD-1, Foshan Nanhai Bochen Polymer New Materials Co., Ltd.

[0028] Toughener C: maleic anhydride grafted styrene-ethylene / propylene-styrene block copolymer, homemade: SEEPS and maleic anhydride were melt blended in a mass ratio of 99:1.

[0029] Toughener D: Maleic anhydride grafted ethylene-octene copolymer, GMG5805, maleic anhydride content of 0.5-1%, Jiayirong; Compatibilizer A: butylene maleate, Jiangsu Runfeng Synthetic Technology; Compatibilizer B: butylene fumarate, Hubei Zhonglong Kangsheng Fine Chemical Co., Ltd.; Compatibilizer C: maleic anhydride, Guangzhou Mohai Trading; Compatibilizer D: N-phenylmaleimide, Guangzhou Yuanda New Materials Co., Ltd.; Compatibilizer E: butyric anhydride, Jiangsu Bosite Chemical Technology; Coupling agent A: aminosilane coupling agent, JH-A110, Hubei Jianghan New Materials; Coupling agent B: methoxysilane coupling agent, trimethoxysilane, Wuhan Xingzhongcheng Technology Co., Ltd.; Coupling agent C: titanate coupling agent, KR-TTS, Kenrich Petrochemical Company, USA; Coupling agent D: aluminate coupling agent, LD-B-1, Lida Chemical; Antioxidant: Antioxidant 1010 and antioxidant 168 are compounded in a weight ratio of 1:2.

[0030] Embodiment and comparative example Preparation method of polyphenylene ether / polyamide alloy: according to the ratio, each component is mixed evenly, and extruded into granules by a twin-screw extruder, the screw speed is 350-400 rpm, and the extrusion temperature is 230-290° C. to obtain polyphenylene ether / polyamide alloy.

[0031] Various test methods: (1) Shrinkage rate: A 200*80*2 mm rectangular plate was injection molded and the length dimension of the material was tested 2 days after injection molding. The result was x mm. The shrinkage rate of the material was calculated according to (200-x) / 200*100%. The dimensional stability of the material was compared by comparing the shrinkage rates.

[0032] (2) Weld mark tensile strength: Referring to ISO 527-1:2019, a 1A weld mark tensile specimen was prepared with a test rate of 10 mm / min. The weld mark strength is used to evaluate the water pressure resistance of the material.

[0033] (3) Hydrolysis resistance: ISO standard Type 1A tensile specimens were placed in a double 85 aging box and aged for 1000 hours. The tensile performance retention rate before and after aging was tested for evaluation. The tensile rate was 10 mm / min.

[0034] Table 1: Weight content of each component of polyphenylene ether / polyamide alloy in Examples 1-7 and test results Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Polyphenylene oxide 38.8 20 30 50 40 31.5 34.4 PA66 24.2 31.5 28.6 PA6 20 PA1010 25 PA 10T 40 PA6T66 30 Fiberglass 20 10 20 30 40 20 20 Toughener A-1 6 8 3 12 10 6 6 Compatibilizer A 1 0.1 0.7 2 1.5 1 1 Coupling Agent A 0.7 0.5 0.2 1.2 1.5 0.7 0.7 Antioxidants 0.2 0.2 0.2 0.3 0.2 0.2 Shrinkage% 0.48 0.69 0.43 0.42 0.41 0.52 0.50 Weld mark strength MPa 60.1 59.2 67.3 68.2 61.3 55.3 58.7 Hydrolysis resistance % 86.1 81.2 87.1 86.2 88.5 83.2 87.4 It can be seen from Examples 1 / 6 / 7 / 8 that the preferred weight ratio of polyphenylene ether to polyamide results in lower shrinkage, better weld mark strength and better hydrolysis resistance.

[0035] Table 2: Weight content of each component of polyphenylene ether / polyamide alloy in Examples 8-14 and test results Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Polyphenylene oxide 40.5 38.8 38.8 38.8 38.8 38.8 38.8 PA66 22.5 24.2 24.2 24.2 24.2 24.2 24.2 Fiberglass 20 20 20 20 20 20 20 Toughener A-1 6 Toughener A-2 6 Toughener A-3 6 Toughener A-4 6 Toughener B 6 Toughener C 6 Toughener D 6 Compatibilizer A 1 1 1 1 1 1 1 Coupling Agent A 0.7 0.7 0.7 0.7 0.7 0.7 0.7 Antioxidants 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Shrinkage% 0.51 0.46 0.43 0.55 0.47 0.48 0.48 Weld mark strength MPa 57.2 61.2 62.2 60.2 57.2 55.2 51.7 Hydrolysis resistance % 85.2 89.2 88.5 84.1 86.5 87.4 85.1 It can be seen from Examples 1 / 9-11 that the technical effect is better when the maleic anhydride grafting rate is optimized.

[0036] It can be further seen from Examples 1 / 9-14 that when the maleic anhydride grafting rate of toughening agents with different main chains is within the preferred range, the shrinkage rate and hydrolysis resistance are better.

[0037] Table 3: Weight content of each component of polyphenylene ether / polyamide alloy in Examples 15-20 and test results Embodiment 15 Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Embodiment 20 Polyphenylene oxide 38.8 38.8 38.8 38.8 38.8 38.8 PA66 24.2 24.2 24.2 24.2 24.2 24.2 Fiberglass 20 20 20 20 20 20 Toughener A-1 6 6 6 6 6 6 Compatibilizer A 1 1 1 Compatibilizer B 1 Compatibilizer C 1 Compatibilizer D 1 Coupling Agent A 0.7 0.7 0.7 Coupling agent B 0.7 Coupling Agent C 0.7 Coupling agent D 0.7 Antioxidants 0.2 0.2 0.2 0.2 0.2 0.2 Shrinkage% 0.46 0.54 0.49 0.46 0.56 0.49 Weld mark strength MPa 62.2 53.2 58.4 58.1 57.4 57.3 Hydrolysis resistance % 89.3 85.5 87.2 88.7 87.1 86.8 It can be seen from Examples 1 / 15 / 16 / 17 that the compatibilizer is preferably a maleate compatibilizer.

[0038] It can be seen from Examples 1 / 18 / 19 / 20 that the coupling agent is preferably a silane coupling agent.

[0039] Table 4: Weight content of each component of comparative polyphenylene ether / polyamide alloy and test results Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Polyphenylene oxide 38.8 26 42 38.8 38.8 38.8 PA66 24.2 37 21 24.2 24.2 24.2 Fiberglass 20 20 20 20 20 20 Toughener A-1 6 6 6 6 6 6 Compatibilizer A 1 1 0 3 1 Compatibilizer E 1 Coupling Agent A 0.7 0.7 0.7 0.7 0.7 0 Antioxidants 0.2 0.2 0.2 0.2 0.2 0.2 Shrinkage% 0.46 0.93 0.37 0.58 0.49 0.46 Weld mark strength MPa 41.8 69.1 35.4 48.2 43.5 52.4 Hydrolysis resistance % 76.3 75.8 92.1 77.7 79.2 81.1 It can be seen from Comparative Example 1 that butyric anhydride cannot be used as a compatibilizer.

[0040] It can be seen from Comparative Example 2 that if the content of PA66 is too high, the shrinkage rate is too high and the hydrolysis resistance is poor.

[0041] It can be seen from Comparative Example 3 that if the content of polyphenylene ether is too high, the weld mark strength is poor.

[0042] It can be seen from Comparative Example 4 that when no compatibilizer is included, the weld mark strength is too low and the hydrolysis resistance is poor due to compatibility defects.

[0043] It can be seen from Comparative Example 5 that if the content of the compatibilizer is too high, the weld mark strength is severely reduced and the hydrolysis resistance is also reduced.

[0044] It can be seen from Comparative Example 6 that if no coupling agent is contained, the weld mark strength is poor and the hydrolysis resistance is not high.

Claims

1. A polyphenylene ether / polyamide alloy, characterized in that: By weight, it includes the following components: Polyphenylene ether 20-50 parts; Polyamide 20-40 parts; Glass fiber 10-40 parts; 3-12 parts of toughening agent; Compatibilizer 0.1-2 parts; Coupling agent 0.2-1.5 parts; Wherein, the weight ratio of polyphenylene ether to polyamide is (1.8-1):1; The compatibilizer is selected from at least one of maleate compatibilizers, anhydride compatibilizers, and N-phenylmaleimide.

2. The polyphenylene ether / polyamide alloy according to claim 1, characterized in that: The weight ratio of polyphenylene ether to polyamide is (1.6-1.2):

1.

3. The polyphenylene ether / polyamide alloy according to claim 1, characterized in that: The compatibilizer is selected from maleate compatibilizers; the maleate compatibilizer is selected from at least one of maleic acid butylene glycol and fumarate butylene glycol; the anhydride compatibilizer is selected from maleic anhydride.

4. The polyphenylene ether / polyamide alloy according to claim 1, characterized in that: The coupling agent is selected from at least one of silane coupling agents, titanate coupling agents, and aluminate coupling agents; preferably, the coupling agent is selected from silane coupling agents; the silane coupling agent is selected from at least one of aminosilane coupling agents and methoxysilane coupling agents.

5. The polyphenylene ether / polyamide alloy according to claim 1, characterized in that: The toughening agent is selected from any one or more of maleic anhydride grafted styrene block copolymers and maleic anhydride grafted ethylene-octene copolymers, wherein the weight content of maleic anhydride is 0.5-3.0wt%, preferably 1.0-2wt%; wherein the styrene block copolymer is selected from at least one of styrene-butadiene-styrene block copolymers, styrene-ethylene / butylene-styrene block copolymers or styrene-ethylene / propylene-styrene block copolymers.

6. The polyphenylene ether / polyamide alloy according to claim 1, characterized in that: The polyphenylene ether resin has a melt index of 4-90 g / 10 min at 315° C. and 10 kg as tested in accordance with standard ISO 1133-1-2011.

7. The polyphenylene ether / polyamide alloy according to claim 1, characterized in that: The polyamide resin is selected from at least one of aliphatic polyamide resins and semi-aromatic polyamide resins; the aliphatic polyamide resin is selected from at least one of PA66, PA46, PA610, PA612, PA56, PA510, PA512, PA910, PA912, PA913, PA914, PA915, PA616, PA936, PA1010, PA1012, PA1013, PA1014, PA1210, PA1212, PA1213, PA1214, PA614, PA613, PA615, PA616, PA5, PA6, PA11, and PA12; the semi-aromatic polyamide is selected from at least one of PA MXD6, PA10T, PA10T1010, PA10T66, PA6T, PA6T66, and PA9T.

8. The polyphenylene ether / polyamide alloy according to claim 1, characterized in that: By weight, the invention further comprises 0-2 parts of auxiliary agents, wherein the auxiliary agents are selected from at least one of antioxidants and lubricants.

9. The method for preparing the polyphenylene ether / polyamide alloy according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components uniformly according to the proportion, extruding and granulating through a twin-screw extruder, with the screw speed being 250-500 rpm and the extrusion temperature being 230-290° C., to obtain a polyphenylene ether / polyamide alloy.

10. Use of the polyphenylene ether / polyamide alloy according to any one of claims 1 to 8, characterized in that: The polyphenylene ether / polyamide alloy is used for preparing water treatment equipment.

Citation Information

Cited By

  • Polyphenylene ether / polyamide alloy, and preparation method therefor and use thereof

    WO2026138408A1